Identificação de plintita e/ou resíduo de saprolito em solos com elevado gradiente textural - Pereira, Mariana Rigueira da Costa (2022)
The identification of mottles such as plinthite and saprolite residue in the soil can be considered a difficult task, both in the field and in the laboratory. The incorrect identification of these redoximorphic features can affect the taxonomic and technical classification of soils, causing damage to society due to the wrong management of soils. The objective of this study was to compare morphological, physical, chemical and mineralogical data in order to identify reddish mottles, possibly plinthites or saprolite residues, that occur in Argissolos Bruno-Acinzentados (Alisols) in southern Brazil. Four soil profiles were selected, being evaluated the horizons Bt, C and Cr. Matrix and mottle samples from each horizon were separated and subjected to morphological, granulometric, mineralogical, total sand fractionation and chemical extractions of Fe (HCl, DCB and OAA) and K (Mehlich-1 and HNO3). Aggregates from each horizon were submitted to the test of submersion in water for 2 and 8 hours and to 5 cycles of wetting and drying. In most of the tested horizons, for the mottled samples, lower clay contents and higher silt and sand contents were quantified, compared to the soil matrix. Iron concentrations in the mottles were higher when compared to the matrix in all extractions. The levels of non-exchangeable K were high, confirming the presence of micas in the source material and suggesting the saprolithic nature of the mottled, with higher levels compared to the matrix. The mineralogy indicated the low degree of alteration of the samples, with abundant presence of 2:1 minerals and feldspars, even in the clay fraction. The saprolite resisted in the water submersion tests, making it difficult to interpret the results for the correct identification between plinthites and saprolite fragments. The morphological field data associated with the results of the tests of submersion in water, of the cycle of wetting and drying, of the dissolution of K and of the mineralogy, indicate the saprolithic nature of the mottles evaluated in all horizons and profiles.